Epigenome‐wide study identifies novel methylation loci associated with body mass index and waist circumference. (July 2015) - Aslibekyan, Stella; Demerath, Ellen W.; Mendelson, Michael; Zhi, Degui; Guan, Weihua; Liang, Liming; Sha, Jin; Pankow, James S.; Liu, Chunyu; Irvin, Marguerite R.; Fornage, Myriam; Hidalgo, Bertha; et al.
<x xml:space="preserve">Abstract</x> Objective To conduct an epigenome‐wide analysis of DNA methylation and obesity traits. Methods DNA methylation was quantified in CD4+ T‐cells using the Illumina Infinium HumanMethylation450 array in 991 participants of the Genetics of Lipid Lowering Drugs and Diet Network. Methylation at individual cytosine‐phosphate‐guanine (CpG) sites as a function of body mass index (BMI) and waist circumference (WC), adjusting for age, gender, study site, T‐cell purity, smoking, and family structure, was modeled. Results Epigenome‐wide significant associations between eight CpG sites and BMI and five CpG sites and WC, successfully replicating the top hits in whole blood samples from the Framingham Heart Study (n = 2, 377) and the Atherosclerosis Risk in Communities study (n = 2, 097), were found. Top findings were in CPT1A (meta‐analysis P = 2.7 × 10−43 for BMI and 9.9 × 10−23 for WC), PHGDH (meta‐analysis P = 2.0 × 10−15 for BMI and 4.0 × 10−9 for WC), CD38 (meta‐analysis P = 6.3 × 10−11 for BMI and 1.6 × 10−12 for WC), and long intergenic non‐coding RNA 00263 (meta‐analysis P = 2.2 × 10−16 for BMI and 8.9 × 10−14 for WC), regions with biologically plausible relationships to adiposity. Conclusions This large‐scale epigenome‐wide study discovered and replicated robust associations between DNA methylation at CpG loci and obesity indices, laying the groundwork for future diagnostic and/or therapeutic applications.